Pengaruh Motivasi Intrinsik dan Ekstrinsik Terhadap Kinerja Karyawan Divisi Network Operations PT XYZ Surabaya - Ghofur, Moh. Abdul; Syairudin, Bambang; Anshori, M. Yusak (UNUSA Press, 2017)
There are five telecommunications operators in Indonesia, including Telkomsel, Indosat Ooredoo, XL Axiata, Tri (3), and Smart Telecom compete to bring the latest 4G technologies as part of corporate strategy into the forefront of mobile communications services. PT XYZ is a multinational company engaged in the field of telecommunications services. The management of PT XYZ Surabaya targeting employee reporting can be increased up to 100%. This study aims to determine how much influence the intrinsic and extrinsic motivation on employee performance PT XYZ Surabaya with SEM-PLS method. The results of this study are extrinsic motivation variable that is most dominant supervision directly affects the performance of employees. Besides the variable performance of employees able to be explained by 0.655 or 65.5% by variable intrinsic motivation and extrinsic motivation, while 34.5% is explained by other variables.